High Areal Capacity Dendrite‐Free Li Anode Enabled by Metal–Organic Framework‐Derived Nanorod Array Modified Carbon Cloth for Solid State Li Metal Batteries - Wang, Tian‐Shi; Liu, Xiaobin; Wang, Yu; Fan, Li‐Zhen (Advanced functional materials, 2021)
Li metal is one of the most promising anode materials for high energy density batteries. However, uncontrollable Li dendrite growth and infinite volume change during the charge/discharge process lead to safety issues and capacity decay. Herein, a carbonized metal–organic framework (MOF) nanorod arrays modified carbon cloth (NRA‐CC) is developed for uniform Li plating/stripping. The carbonized MOF NRAs effectively convert the CC from lithiophobic to lithiophilic, decreasing the polarization and ensuring homogenous Li nucleation. The 3D interconnected hierarchal CC provides adequate Li nucleation sites for reducing the local current density to avoid Li dendrite growth, and broadens internal space for buffering the volume change during Li plating/stripping. These characteristics afford a stable cycling of the NRA‐CC electrode with ultrahigh Coulombic efficiencies of 96.7% after 1000 h cycling at 2 mA cm−2 and a prolonged lifespan of 200 h in the symmetrical cell under ultrahigh areal capacity (12 mAh cm−2) and current (12 mA cm−2). The solid‐state batteries assembled with the composite Li anode, high‐voltage cathode (LiNi0.5Co0.2Mn0.3O2), and composite solid‐state electrolyte also deliver excellent cyclic and rate performance at 25 °C. This work sheds fresh insights on the design principles of a dendrite‐free Li metal anode for safe solid‐state Li metal batteries. Dendrite‐free Li anodes can be achieved through a carbonized Co‐based zeolitic imidazolate framework nanorod arrays modified carbon cloth (NRA‐CC). Owing to the synergistic effect of the interconnected carbon cloth and lithiophilic Co–N–C NRAs, NRA‐CC can regulate the Li plating/stripping behavior and withstand high areal capacity and current density. The composite Li anode is successfully applied in solid‐state Li metal batteries.